Pemodelan ARDL Pengaruh Ekspor- Impor terhadap Inflasi di Jawa Timur - Reta Wanda Mardaningrum; Sri Harini; Erna Herawati (Jurnal Riset Mahasiswa Matematika, 2025)
The Autoregressive Distributed Lag (ARDL) approach is a time series analysis method that enables the examination of short- and long-term relationships between variables, even when the variables have different levels of stationarity. This study aims to analyze the influence of export and import values on inflation in East Java using standardized monthly data from the Central Bureau of Statistics (BPS) East Java, covering the 2018–2023 period. The selected ARDL model revealed cointegration, indicating significant long-term relationships among the variables. The best model was identified with an F-statistic value of 6.4036, an R-squared value of 0.8163, and the lowest Akaike Information Criterion (AIC). The results demonstrate that export activities, particularly non-oil and gas exports, tend to suppress inflation in the long term, while oil and gas imports exhibit a strong positive influence on inflation. Standardized data were used in this analysis to ensure consistent representation of relationships among.